METHODS FOR TEACHING INTERPRETING ECONOMIC TEXTS AT GUIDE GROUPS - Khujanazarova Nozima Omonjonovna (American Journals Publishing, 2023)
This article discusses various methods for teaching interpreting economic texts in guide groups. The article highlights the importance of economic knowledge in today's world and the need for guides to learn how to interpret economic texts. The methods section presents different techniques for teaching economic interpretation, such as active reading, discussion groups, and practical exercises. The results section examines the effectiveness of these methods based on their impact on the participants. The discussion section provides an in-depth analysis of the results and discusses the challenges encountered during the teaching process. The article concludes with suggestions for improving the teaching of economic interpretation in guide groups.
Keywords: Interpreting economic texts, guide groups, active reading, discussion groups, practical exercises, effectiveness, challenges.